2011
DOI: 10.1016/j.ydbio.2010.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Ectodermal WNT/β-catenin signaling shapes the mouse face

Abstract: The canonical Wnt/β-catenin pathway is an essential component of multiple developmental processes. To investigate the role of this pathway in the ectoderm during facial morphogenesis, we generated conditional β-catenin mouse mutants using a novel ectoderm-specific Cre recombinase transgenic line. Our results demonstrate that ablating or stabilizing β-catenin in the embryonic ectoderm causes dramatic changes in facial morphology. There are accompanying alterations in the expression of Fgf8 and Shh, key molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
98
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(102 citation statements)
references
References 39 publications
3
98
1
Order By: Relevance
“…However, activation of the transgenic live actin reporter R26R:Venus–actin 32 in ectoderm using an early ectoderm-specific Cre recombinase, Crect 33 , revealed that, although cell interface lengths oscillated, average AP cell interfaces did not shorten progressively during intercalation at the DV midline (average 25 som. stage AP cell interface length at T = 0 min and T = 120 min: 7.44 μm ± 0.34 μm (s.e.m.)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, activation of the transgenic live actin reporter R26R:Venus–actin 32 in ectoderm using an early ectoderm-specific Cre recombinase, Crect 33 , revealed that, although cell interface lengths oscillated, average AP cell interfaces did not shorten progressively during intercalation at the DV midline (average 25 som. stage AP cell interface length at T = 0 min and T = 120 min: 7.44 μm ± 0.34 μm (s.e.m.)…”
Section: Resultsmentioning
confidence: 99%
“…No. CDB0218K, http://www.cdb.riken.jp/arg/reporter_mice.html 32 ); Crect 33 ; ZEG (Jackson Laboratory, Tg(CAG–Bgeo/GFP)21/Lbe/J); β-catenin flox (Jackson Laboratory, B6.129-Ctnnb1 tm2Kem /KnwJ ); Fgfr2 flox (Jackson Laboratory, STOCK Fgfr2 tm1Dor /J). Genotyping primers are available on the Jackson Laboratory website for each mouse line.…”
Section: Methodsmentioning
confidence: 99%
“…Previous reports have shown that reduced canonical WNT signaling through deletion of Wnt9b or Lrp6 during craniofacial development leads to facial deformity, including CL/P, in mice (13,14). Furthermore, a strong correlation between ectodermal canonical WNT signaling and nasal process growth has been reported (39). From our observations of the patterns of SHH signaling (Ptch1-LacZ) and canonical WNT signaling (TOPgal) during craniofacial development, we found that those 2 signaling pathways complement each other during facial development (Supplemental Figure 4).…”
Section: Disruption Of the Shh Signaling Gradient During Craniofacialmentioning
confidence: 98%
“…Neural crest cells make up the majority of the cranial mesenchyme and make numerous contributions to the craniofacial complex, most notably to the facial mesenchyme and skeletal elements. Second, we utilized the Crect driver [22] to target recombination to cells within the surface ectoderm (Fig 1C and 1D). The developing surface ectoderm houses many signaling centers that are important for directing craniofacial development such as the frontonasal ectodermal zone (FEZ) and the nasal pits [2327].…”
Section: Resultsmentioning
confidence: 99%